A parallel duplicate address detection (PDAD) mechanism to reduce handoff latency of mobile internet protocol version 6 (MIPV6) - Masud, M. H.; Anwar, Farhat; Mohamed, Omer Mahmoud; Bari, S.M. Sadakatul; Salami, A. F. (2011)

(untitled)
Next Generation Networks (NGN) are envisioned to be fully Internet Protocol (IP) based so that users can experience high quality and ubiquitous communication. In order to realize this, Internet Engineering Task Force (IETF) is taking advantage of Mobile Internet Protocol version 6 (MIPv6) because it has more suitable features than MIPv4. However, MIPv6 is not widely deployed due to handoff latency and other limitations. This causes packet loss and degrades the Quality of Service (QoS) for real-time applications. MIPv6 handoff latency includes link layer establishment delay, movement delay, address auto-configuration delay and binding update/registration delay. Duplicate Address Detection (DAD) is performed during address auto-configuration which takes around 70% of the time for the total handoff procedures. In order to reduce this handoff latency, a Parallel DAD (PDAD) model is proposed for reducing packet loss. The key idea behind this model is that a Mobile Node (MN) solicits for a router advertisement (RA) in parallel to its neighbor routers before leaving the previous point of attachment.